2005
DOI: 10.1002/fld.970
|View full text |Cite
|
Sign up to set email alerts
|

Vortex shedding from a square cylinder in presence of a moving wall

Abstract: SUMMARYA numerical study on the ow past a square cylinder placed parallel to a wall, which is moving at the speed of the far ÿeld has been made. Flow has been investigated in the laminar Reynolds number (based on the cylinder length) range. We have studied the ow ÿeld for di erent values of the cylinder to wall separation length. The governing unsteady Navier-Stokes equations are discretized through the ÿnite volume method on a staggered grid system. A SIMPLE type of algorithm has been used to compute the disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…They found that the kinematic condition of the wall does not affect the gross flow characteristics, such as the Strouhal number and lift force, but does significantly alter the trajectory of the vortices behind the cylinder. Bhattacharyya and Maiti (2005) simulated the two-dimensional laminar flow past a square cylinder placed parallel to a moving wall; they found that vortex shedding occurs even at the very small gap ratio of G/D ¼ 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the kinematic condition of the wall does not affect the gross flow characteristics, such as the Strouhal number and lift force, but does significantly alter the trajectory of the vortices behind the cylinder. Bhattacharyya and Maiti (2005) simulated the two-dimensional laminar flow past a square cylinder placed parallel to a moving wall; they found that vortex shedding occurs even at the very small gap ratio of G/D ¼ 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…Kumarasamy and Barlow [9] simulated the flow over a half cylinder close to a moving wall and compared the results with those of stationary wall. Bhattacharyya and Maiti [10] simulated the two-dimensional laminar flow past a square cylinder placed parallel to a moving wall. They found that vortex shedding occurs even at a very small gap ratio of G=D D 0.1.…”
Section: Introductionmentioning
confidence: 99%